2019
DOI: 10.14687/jhs.v16i4.5860
|View full text |Cite
|
Sign up to set email alerts
|

Perceived Freedom in Leisure Scale-25: Testing the construct validity for university students

Abstract: Leisure behaviour is an important study area of the literature recently. In apprehending leisure behaviour, perceived freedom in leisure is a significant dimension. The aim of the study is to test validity of "Perceived Freedom in Leisure Scale (PFLS)" by confirmatory factor analysis (CFA). Study group of this descriptive research consists of 228 university students. Reliability was calculated by internal consistency coefficient Cronbach's Alpha. As a result of the CFA, modification indexes were examined and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…Similarly, Akyüz and Türkmen (3) and Tektaş et al (21) stated that women's leisure attitudes were stronger and higher than men. When the literature was (15) emphasized that men were more active and comfortable in recreational choices thanks to such society supported structures as work, family, social responsibilities whereas women's recreational choices and options were more limited due to roles they adopted. Thapa, Confer and Mendelson (22) reported that men participated in more activities in recreational areas than women; which -in other words-means that women were exposed to more restrictions in leisure activities.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Akyüz and Türkmen (3) and Tektaş et al (21) stated that women's leisure attitudes were stronger and higher than men. When the literature was (15) emphasized that men were more active and comfortable in recreational choices thanks to such society supported structures as work, family, social responsibilities whereas women's recreational choices and options were more limited due to roles they adopted. Thapa, Confer and Mendelson (22) reported that men participated in more activities in recreational areas than women; which -in other words-means that women were exposed to more restrictions in leisure activities.…”
Section: Discussionmentioning
confidence: 99%